Відповідь:
Пояснення:
1)sin(π/4+α)=cos(π/4-α);⇒
sin(π/4+α)=sin(π/2-π/2+π/4+α)=
=cos(-π/2+π/4+α)=cos(-π/4+α)=cos(π/4-α).2)tg(п/4-α)=ctg(п/4+α)
Используя формулу приведения tg(π/2-β)=ctgβ , получим
при β=π/4+α tg(π/2-β)=tg(π/2-(π/4+α))=tg(π/2-π/4+α))=tg(π/4-α)
ctgβ=ctg(п/4+α)⇒tg(п/4-α)=ctg(п/4+α). Тождество доказано.2)по формулам
tg(x-y)=(tgx-tgy)/(1+tgx-tgy)
tg(x+y)=(tgx+tgy)/(1-tgx-tgy)
tgп/4=1
ctgx=1/tgx
тогда
tg(п/4-a)=(tg(п/4)-tga)/(1+tg(п/4)-tga)=(1-tga)/(1+tga)
tg(п/4+a)=(tgx+tgy)/(1-tgx-tgy)=(1+tga)/(1-tga)
ctg(п/4+a)=1/tg(п/4+a)=1/((1+tga)/(1-tga))=(1-tga)/(1+tga)=tg(п/4-a)
⇒
ctg(п/4+a)=tg(п/4-a)
Автор:
rockoestesДобавить свой ответ
Предмет:
ЛитератураАвтор:
mckennagarzaОтветов:
Смотреть
Предмет:
Английский языкАвтор:
susie qОтветов:
Смотреть
Предмет:
ЛитератураАвтор:
frazierОтветов:
Смотреть